2019
DOI: 10.3892/ol.2019.10109
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of malignant brain tumor domain containing protein 1 predicts a poor prognosis of prostate cancer

Abstract: Malignant brain tumor domain containing protein 1 (MBTD1) is a member of the polycomb group protein family that is associated with tumorigenesis. The present study investigated the role of MBTD1 within defined clinicopathological parameters and the prognosis of patients with prostate cancer (PCa). A human tissue microarray containing samples from 71 patients with PCa and seven healthy donors was employed for immunohistochemistry (IHC). The clinicopathological characteristics and prognostic value of MBTD1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…For example, Luo et al (2013) showed that depletion of MBTD1 in oocytes activated the cell cycle checkpoint protein Chk1 and led to cell cycle arrest. Further, regulation of HESC proliferation by MBTD1 is in line with published work that indicated that MBTD1 controls growth of multiple cancer cells (de Rooij et al, 2016;Hoang et al, 2018;Yamamoto et al, 2018;Fu et al, 2019;Plesa and Sujobert, 2019;Wu et al, 2019). Thus, based on our findings and published work, we posit that MBTD1 functions in HESC decidualization through multiple cellular mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Luo et al (2013) showed that depletion of MBTD1 in oocytes activated the cell cycle checkpoint protein Chk1 and led to cell cycle arrest. Further, regulation of HESC proliferation by MBTD1 is in line with published work that indicated that MBTD1 controls growth of multiple cancer cells (de Rooij et al, 2016;Hoang et al, 2018;Yamamoto et al, 2018;Fu et al, 2019;Plesa and Sujobert, 2019;Wu et al, 2019). Thus, based on our findings and published work, we posit that MBTD1 functions in HESC decidualization through multiple cellular mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we found that circZNF236 was able to absorb miR-145-5p to increase the expression of MBTD1. In line with this observation, MBTD1 expression has been shown to be enhanced in prostate cancer tissues and is associated with aggressive clinicopathological characteristics [27] . Indeed, we found that increased expression of MBTD1 could rescue the inhibitory effects of circZNF236 silencing on malignant properties of OSCC cells.…”
Section: Discussionmentioning
confidence: 73%
“…The percentage of positive cells was scored as follows: <5% (score: 0), 6-25% (score:1), 26-50% (score: 2), 51-75% (score: 3) and >75% (score: 4). The immunoreactivity scores (IRS) were calculated by adding the immunostaining percentages and immunostaining intensity scores together [28].…”
Section: Evaluation Of Immunostaining Resultsmentioning
confidence: 99%